Correlation between Leptin with Diastolic Function in Young Adult Obesity - Fauzi Akira Nugraha; M. Rizki Akbar; Toni M. Aprami; Januar W. Martha (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Background: Obesity is one of the global health problems with increasing prevalence, and the complication is related to the alteration of the left ventricle. An obese person without symptoms has impaired diastolic function compares to a normal population, but the mechanism is still unclear. One of the evolving theories is caused by chronic inflammation, characterized by the increase of proinflammatory adipocytokines in an obese person. Leptin is a chronic inflammatory marker which is synthesized by all adipose tissues and has a positive correlation with the body mass index. Leptin level are influenced by age except young adult group. The aim of this study is to investigate the correlation between leptin level and diastolic function of the left ventricle in youngadult obese.Method: This study was conducted in a single centre with cross-sectional design. The subject of this study consists of all young adult obese, worked in Dr. Hasan Sadikin General Hospital, between June-August 2018. The diastolic function of the left ventricle was measured by examining the ventricle relaxation (E/mean e’) by tissue doppler imaging method. The examination of leptin level was done by sandwich-ELISA testmethod. Pearson correlation test was done to assess the correlation between those two.Result: This study consisted of 38 patients with the mean of age 30.75±7.25 years old, 68% were males. The mean score of E/mean e’ was 6.49±3.02 ng/mL and the median of leptin was 13.95 (9.1–25.4) mg/L. After data log transformation of leptin was done, there was a significant positive correlation (r= 0.5892, p<0.001) between leptin level and E/mean e’.Conclusion: There was a significant correlation between the level of leptin and diastolic function of the left ventricle in young adult obese.